High performance humidity sensor and photodetector based on SnSe nanorods - Pawbake, Amit S.; Jadkar, Sandesh R.; Late, Dattatray J. (Materials Research Express, 2016)
Tin selenide (SnSe) nanorods were synthesized using a. one-step solvothermal route and. their. humidity sensing and photodetection performance at room temperature were investigated. The results depict. that SnSe nanorod-based humidity and photosensors have. good long-term stability, are. highly sensitive and have. fast response and recovery times. In the. case of the. humidity sensor it was observed that the resistance of the films decreased. with increasing relative humidity (RH). The humidity sensing behaviors were investigated in the range. 11-97% RHat room temperature. A. response time of similar to 68 s and recovery time of similar to 149 s were observed for. the humidity sensor. The photosensing behavior showed. typical response/recovery times of similar to 3 s with highly reproducible behavior.